Cold sprayed FeCoNiCrMn High Entropy Alloy (HEA) coating: microstructure and tribological property - Lupoi, Rocco; Yin, Shuo (ASM International, 2019)
High entropy alloys (HEAs) are of great interest in the community of materials science and engineering due to their unique phase structure. They are constructed with five or more principal alloying elements in equimolar or near-equimolar ratios. Therefore, HEAs can derive their performance from multiple principal elements rather than a single element. In this work, solid-state cold spraying (CS) was applied for the first time to produce a FeCoNiCrMn HEA coating, and also mixed with Al2O3 in a separate experiment. The experimental results confirm that CS can be used to produce a thick HEA coating with low porosity. As a low-temperature deposition process, CS completely retained the HEA phase structure in the coating without any phase transformation. The characterization also reveals that the grains in the CSed HEA coating had experienced significant refinement as compared to those in the as-received HEA powder due the occurrence of dynamic recrystallization at the highly deformed interparticle region. Due to the increased dislocation density and grain boundaries, CSed HEA coating was much harder than the as-received powder. The tribological study shows that the CSed FeCoNiCrMn HEA coating resulted in lower wear rate than laser cladded HEA coatings.
ITSC 2019 - Proceedings of the International Thermal Spray Conference
PUBLISHED
Yokohama (Japan)
Keywords: Cold spray; Thermal spray; High entropy alloys